Planning Commission Back Ground Material 1964 - Planning Commission (Planning Commission, 1964)
In order to ensure that the Indian Cooperative movement develops as one integrated movement and on sound lines so as to make it a powerful force in the economy of the country, a number of committees of inquiry and study teams have been constituted since 1895 which went into details of the various problems faced in the field of. cooperation and suggested ways and means to develop wider establishment of the cooperative movement in India. A list of such committees together with the objectives before them or their terms of reference is given below.
Planning Commission
Planning Commission
Keywords: Labour Employment Division; land Reform Division; Perspective Planning Division; Plan Coordination Section; Programme Administration Division; Public Cooperation Division; Resources and Scientific Research; Research Programme Committee; Social Welfare Division; Village & Small Industries Division; Committee On Plan Projects; Programme Evaluation Organization